2015
DOI: 10.1186/s12943-015-0414-1
|View full text |Cite
|
Sign up to set email alerts
|

Stratifin accelerates progression of lung adenocarcinoma at an early stage

Abstract: BackgroundsAdenocarcinoma in situ (AIS) of the lung has an extremely favorable prognosis. However, early but invasive adenocarcinoma (eIA) sometimes has a fatal outcome. We had previously compared the expression profiles of AIS with those of eIA showing lymph node metastasis or a fatal outcome, and found that stratifin (SFN, 14-3-3 sigma) was a differentially expressed gene related to cell proliferation. Here, we performed an in vivo study to clarify the role of SFN in initiation and progression of lung adenoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 17 publications
2
49
0
Order By: Relevance
“…We had previously found that depletion of SFN decreased cell growth in vitro and tumor progression or development in vivo, suggesting that SFN might be a promising therapeutic target for lung adenocarcinoma (12). Here, we revealed that SFN enhances tumor progression through binding with SKP1 and blocking of oncoprotein ubiquitination.…”
Section: Interaction Of Sfn With Skp1 Is Competitive With Fbw7mentioning
confidence: 59%
See 2 more Smart Citations
“…We had previously found that depletion of SFN decreased cell growth in vitro and tumor progression or development in vivo, suggesting that SFN might be a promising therapeutic target for lung adenocarcinoma (12). Here, we revealed that SFN enhances tumor progression through binding with SKP1 and blocking of oncoprotein ubiquitination.…”
Section: Interaction Of Sfn With Skp1 Is Competitive With Fbw7mentioning
confidence: 59%
“…Moreover, its overexpression is significantly associated with poorer prognosis in patients with breast cancer (8), hepatocellular carcinoma (9), colorectal carcinoma (10), and endometrial carcinoma (11). Our in vitro and in vivo functional analysis has also indicated that SFN regulates cell-cycle progression in a positive manner and promotes the progression of lung adenocarcinoma (12). Importantly, 30% of SFN-transgenic mice with lung-specific expression of human SFN spontaneously developed lung tumors, suggesting that SFN is a potent oncogene.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Non-gastric cancer SFN speed up lung adenocarcinoma development in an early stage (Shiba-Ishii et al, 2015).…”
Section: -3-3 Protein Sigma (Sfn)mentioning
confidence: 99%
“…11 Elevated expression of 14-3-3σ has been shown to arrest the cell cycle at the G2 phase of colon and breast cancer cells. 12,13 By contrast, in an oncogenic role, ectopic expression of 14-3-3σ has been reported to promote proliferation of lung cancer cells, 14 and motility or invasion of colon 15 and breast 16 cancer cells. These different roles have also been demonstrated in a clinical setting.…”
Section: Introductionmentioning
confidence: 98%